2017
DOI: 10.5433/1679-0359.2017v38n3p1417
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of massai grass fertilized with phosphorus and nitrogen and its influence on intake and weight gain of sheep under rotational grazing on quartzipsamment soil

Abstract: The effects of phosphate and nitrogen fertilization on aspects of forage composition and ruminal fermentation were separately evaluated pre- and post-grazing, in addition to the dry matter intake and weight gain of sheep grazing Panicum maximum cv. Massai under a rotational system on Quartzipsamment soil. The aim was to evaluate the effect of fertilization with different levels of phosphorous (50 and 200 kg P2O5/ha) and nitrogen (100 and 400 kg N/ha) compared to unfertilized control soil. The experiment was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…Some studies suggest that in vitro and in vivo digestibility of organic matter increases with the rainy season (Vargas Junior et al, 2013;Silva et al, 2017), and others show that water stress did not significantly affect organic matter digestibility (OMD), (Fariaszewska et al, 2020). The findings in this research suggested that ADF decreased similar to that reported by Larsen et al (2021) and IVDMD increased slightly during the dry season vis-à-vis the rainy season.…”
Section: Seasonsupporting
confidence: 72%
See 1 more Smart Citation
“…Some studies suggest that in vitro and in vivo digestibility of organic matter increases with the rainy season (Vargas Junior et al, 2013;Silva et al, 2017), and others show that water stress did not significantly affect organic matter digestibility (OMD), (Fariaszewska et al, 2020). The findings in this research suggested that ADF decreased similar to that reported by Larsen et al (2021) and IVDMD increased slightly during the dry season vis-à-vis the rainy season.…”
Section: Seasonsupporting
confidence: 72%
“…09, 6.24, 6.13, 6.72, 7.82, and 8.30%, respectively. These values were higher than those found in commercial cultivars in important tropical livestock areas (dos Costa et al, 2017;Silva et al, 2017;da Silva et al, 2018). However, in the same research location where this experiment took place, and with a similar number of regrowing days and average height in Massai, Ruiz et al (2015) showed 14.20% CP.…”
Section: Seasonmentioning
confidence: 58%
“…Several factors such as management, regrowth age, fertilization, cut height, phenological aspects, growth under shade and seasons might have a signi cant effect in the nutritional value of forages (Van Soest, 1982Velásquez et al, 2010, Santiago-Hernández et al, 2016, Silva et al, 2017, Coêlho et al, 2018, Vasconcelos et al, 2019, Schnellmann et al, 2020and Tesk et al, 2020 which affects digestibility in animals (Valente et al, 2010). Variability in structural carbohydrates (NDF, ADF) composition of the M. maximus collection may be in uenced by characteristics related to accession own physiological and metabolic aspects as the conversion e ciency of nitrogen and the rate of owering (Costa et al, 2017) which might generate a wide range of available accessions and could be used in plant breeding programs (Deo et al, 2020) to generate or select materials with the best IVDMD (Barahona & Sánchez-Pinzón, 2005) Protein content reduction during low precipitation periods might be caused by the lack of production of new leaves and tillers during dry season.…”
Section: Discussionmentioning
confidence: 99%
“…Gurgel et al (2017) observed even lower values (5.5%) in Massai grass in times of water restriction, according to these authors this makes the supplementation necessary for a better productive performance. Silva et al (2017) evaluating doses of up to 100 kg ha -1 and 50 kg ha -1 of N and P2O5 respectively, in the same area of Massai grass where this experiment was carried out, found CP values of 7.06% in the water period, close to the 7.03% observed by Costa et al (2017) The production and structure of the pasture did not present difference for the evaluated treatments, indicating that the management adopted in the pasture was the same in the used area. Managing Massai grass height at 35.58 cm, the dry mass production was 5512.41 kg ha -1 (Table 4), a value lower than the forage mass production obtained in this same area in the water period (6600 kg ha -1 ) with similar management and fertilization height (Cardoso et al, 2019), which was expected due to the low precipitation of this time (Table 1).…”
Section: Resultsmentioning
confidence: 99%